Investment guide for low-emission rice in the Mekong Delta, Vietnam - Nelson, Katherine; Tran Van The; Le Hoang Anh; Bui Tan Yen; Wollenberg, Eva Karoline; Sander, Björn Ole (2023)
Rice production is an integral commodity to global food security, but it also contributes considerably to greenhouse gas emissions (GHG). There are a variety of options to mitigate GHG emissions from paddy rice production but the impacts and opportunities to finance such activities are not well-known or well-understood for global investors, and much remains to be done to ensure that international climate finance can be used to attract private sector investments into sustainable agriculture. This guide provides promising GHG mitigation options and analyses of cost and benefits to develop an investment plan for Mekong Delta in Vietnam. Investment de-risking strategies are also included in this publication.